Dynamic characteristics of track-ballast-silty clay with irregular vibration levels generated by high-speed train based on DEM. (30th October 2016) - Zhang, Zhihua; Zhang, Xiedong; Qiu, Hongsheng; Daddow, Mohammad
Highlights: Track-ballast-silty clay model established by discrete element method. Irregular vibrations executes directly and simply on tracks by B_YFAP(BP) command. Settlement of the track attributes mostly to horizontal and vertical displacements of ballast stones. Higher speed the train runs, higher acceleration the track gets. Concrete slab has advantages in reducing the settlement and vibrations of tracks. Abstract: A two-dimensional ballasted railway tracks model utilizing the discrete element method (DEM) with PFC is proposed to analyze the dynamic characteristics of the concrete sleeper, clustered ballast stones and the silty clay subgrade under irregular vibration levels caused by train passes the track. Another model for reducing the track vibrations by using concrete slab is conducted. This is novel to analyze the influence of irregular vibration levels on railway track by using DEM and to consider a simple solution for high settlement and vibrations of track. The concrete sleeper is idealized as a collection of expansive bonded particles assembled together. Ballast stones are modeled as clusters of rock's properties with different particle numbers. The subgrade has the micromechanical properties of silty clay. The micro parameters of concrete slab are the same as those of sleeper. Analyses have done to reveal the microscale interaction in each layer with different train speed. It demonstrates that the velocity of particles decreases with the depth location increases. As irregular vibration levels progressed, the discrete ballast stones disperse horizontally in certain area. With the increase of train speed, the acceleration of the track increases, however, putting up the same velocity curves. The effect of impact load on railway foundation decreases with the depth increases, especially when the ballast dissipates the kinetic energy. Concrete slab has advantages in reducing the settlement and vibrations of the track.